The functional domains of the Drosophila morphogen dorsal: evidence from the analysis of mutants. - Isoda, K.; Roth, S.; Nusslein-Volhard, C. (Genes & Development, 1992)
The dorsal (dl) protein is a member of the Rel family of transcription factors. It is distributed in a nuclear concentration gradient along the dorsoventral axis of Drosophila embryos and activates or represses a discrete set of zygotic genes in a concentration-dependent manner. The nuclear uptake of the dl protein is stimulated by products of the dorsal group genes but inhibited by the cactus (cact) product. To analyze the functional domains of the dl protein, we sequenced 11 dl alleles and studied their interaction with cact. Four of these alleles were found to result in carboxy-terminal truncations of the protein. A deletion of 80 carboxy-terminal amino acids abolishes the ability of dl protein to activate the expression of mesodermal genes. Larger deletions also affect the repressor function of dl. However, a protein consisting only of the Rel homologous region still acts as a weak repressor of zerknüllt transcription. A missense mutation in the presumptive DNA-binding domain causes a complete lack-of-function phenotype in trans to a deficiency but exerts a dominant-negative effect in trans to a wild-type copy of dl. These and genetic data with the alleles that produce truncated proteins indicate that dl oligomerizes. The proteins truncated at the carboxy-terminal end show increased levels of nuclear uptake dorsally, but they still respond to the cact-mediated inhibition of nuclear transport. Therefore, carboxy-terminal sequences influence the cytoplasmic retention, although a domain of dl-cact interaction residues in the amino-terminal portion.